Star Attractions - Symphony in the Flint Hills, Inc. (Symphony in the Flint Hills, 2019)
Introduction: On a dark night, a person with good vision can see for twenty quadrillion miles and as many as 2,500 stars without optical instruments. Astronomers estimate that the Milky Way galaxy has a trillion stars.